Modern-day Universities and Regional Development - Bence Zuti (IX. KHEOPS Nemzetközi Tudományos Konferencia, 2014)
Nowadays it is quite evident that knowledge-based society necessarily involves the revaluation of human and intangible assets, as the advancement of local economies significantly depend on the qualitative and quantitative characteristics of human capital[Lundvall, 2004]. As we can instantaneously link the universities as main actors in the creation of highly-qualified labour force, the role of universities increases parallel to the previously mentioned progresses. Universities are the general institutions of education, however i nthe need of adaptation to present local needs, their activities have broadened in the past decades [Wright et al, 2008; Etzkowitz, 2002]. Most universities experienced a transition period in which next to their classic activities, namely education and research, so called third mission activities also started to count, thus serving many purposes of economy and society.
Keywords: I23; O31; R11; 330; "Fourth Generation" Universities; Regional Development